CRUDE POLYSACCHARIDES EFFECT OF Coriolus versicolor ON Mycobacterium fortuitum-INDUCED IMMUNE DYSFUNTION IN MICE - Wahyuningsih, Sri Puji Astuti; Winarni, Dwi; Darmanto, Win; S., Sugiharto; Sajidah, Elma Sakinatus; Dewi Atika, Baiq Naili (Malaysian Journal of Science, 2019)
Coriolus versicolor contains crude polysaccharides which have Î²-glucan active ingredients. It can activate granulocyte, monocyte, and macrophage. Administration of crude polysaccharide of C. versicolor against bacterial infection is hypothesized to increase immune response. This study assessed the crude polysaccharides activity of C. versicolor in improving immune response after induction of non-tuberculosis mycobacteria, Mycobacterium fortuitum. Animal model was female mice strain BALB/c aged 8-10 weeks. A crude polysaccharide of C. versicolor was administered before and/or after the bacteria infection for 10 days at a dose of 50 mg/kg body weight. Mice exposure to M. fortuitum was performed twice at a dose of 0.5 Mc. Farland. After crude polysaccharides treatment, both serum and peritoneal fluid were isolated. All data collected were analyzed statistically using ANOVA and Duncan test. Oral administration of crude polysaccharide was found to increase phagocyte number (P<0.05, from crude polysaccharides administration before-after infection), improve phagocytic activity (P<0.05, from crude polysaccharides administration before infection), raise both IFN-g and antibody level (P<0.05, from crude polysaccharides administration after and before-after infection), and it caused TNF-Î± levels to tend to a normal concentration (P>0.05, TNF-Î± levels after crude polysaccharides administration were relatively the same as controls). Administration of crude polysaccharides of C. versicolor could enhance non-specific immune response, specific immune response, and pro-inflammatory cytokine in mice infected by M. fortuitum. These results suggested that crude polysaccharides of C. versicolor may be applied as an effective immunostimulatory agent.